Haar Cascade Algorithm On Mask Detection System Based On Distance In Facing The Normal Era - Jemakmun makmun Jemakmun; Rudy Suhirja (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
The COVID-19 outbreak has hit almost the whole world, including Indonesia which has become a disease outbreak in early 2020. Therefore, currently, various places have enforced regulations to comply with health protocols by using masks. So all South Sumatra must follow health protocols by wearing masks and maintaining distance. So the program for making this Mask Detection System is one way to overcome public awareness, especially among Bina Darma University students about the importance of using masks today. In the case of making this mask detection system program, the researchers used Python and the Haar Cascade Algorithm. From experiments using the Haar Cascade method, this system can detect people who use masks and do not use masks. This test is also done by inputting images or videos. The results of the study that, based on distance and angle, the estimated minimum distance for this mask detection application is 25 cm and the maximum is 150 cm will produce maximum mask detection results and based on distance, the estimated distance is 50 cm to 300 cm, the design of the detection system can recognize the maximum face